PERENCANAAN TARIF IDEAL PENGIRIMAN BARANG BERDASARKAN METODE PERHITUNGAN BIAYA OPERASIONAL KENDARAAN (BOK) - Mulyati, Erna; Alif, Aghitsna Iqbal (Muhammadiyah University Press, 2013)
PT Syncrum Logistics is a company engaged in the expedition of freight transportation services 3PL (Third Party Logistics), which delivery goods from one place to the destination area by land (On Road) by using a fleet of wings box trucks. PT Syncrum Logistics has more than 80 wings box fleet which are owned by the box itself. One is a box type truck wings are often used for service delivery to Milkrun Cibitung. On the imposition of tariffs for one-time delivery of goods on the route there is a difference with Milkrun Cibitung previous rate calculation that originally was Rp 800.802, - to be decreased to Rp 522.700,-. Tariff of Rp 522.700 based solely on the price offer made by the customer on the marketing side. That price has not reached the ideal rate of the company. From the description above, the calculation for ideal freight rates by route Milkrun Cibitung uses the Vehicle Operating Costs. Calculating the Vehicle Operating Costs must first determine the fixed costs, variable costs and the determination of the basic rate and calculation of the costs incurred each year, month and day, and the benefits to be achieved by the company. Difference obtained is Rp 229.837,- from the initial rate off price minimum negotiable to do between Rp 800.802 to Rp. 707.612/28 pallets (Full Load).